Nonsyndromic gemination-associated microdontia: A report of an unusual case - Laboni Ghorai; Mayukh Bhattacharya (Wolters Kluwer Medknow Publications, 2023)
Tooth gemination is a dental anomaly that results from an incomplete attempt of a single tooth germ to separate during morphodifferentiation stage of odontogenesis, and it usually exhibits a large bifid crown with a single common root and root canal. This developmental anomaly more commonly affects primary dentition than the permanent, with an infrequent occurrence reported of posterior teeth. Among the posterior teeth, mandibular second premolars have reportedly shown an elevated possibility of agenesis, delayed odontogenesis, and variability of crown morphology. Both unilateral and bilateral cases of isolated macrodontia of mandibular second premolar secondary to gemination or fusion have been reported, but there is no evidence of microdontia associated with gemination in the literature till date. This case presentation reports an unusual case of isolated unilateral gemination-associated microdontia of the left mandibular second premolar in a nonsyndromic patient.